Pemanfaatan Hikayat Melalui Model Pembelajaran Contextual Teaching and Learning Sebagai Bentuk Edukasi Tentang Karya Sastra di Kelas X Tekhnik Komputer Jaringan (TKJ) SMK Bina Jaya Palembang - Rani Syafitri; Hastari Mayrita (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
Hikayat as a classic work is often not widely understood by vocational school (Vocational High School) students who are related to various aspects such as language, culture and the historical context contained in the saga. Therefore, the researcher wants to solve the problem by researching directly into a class which also carries out teaching assistance activities in accordance with the requirements for completing semester 7. The subject of this research uses classroom action research. The subjects in this research were class X-I Computer Network Engineering (TKJ) students at Bina Jaya Vocational School. This research aims to find out how the use of saga as the level of knowledge of class (Computer Network Engineering), and how after carrying out the Contextual Teaching and Learning (CTL) learning model in analyzing the values contained in the saga text. This research uses a qualitative approach with descriptive methods. The data obtained was carried out through three cycles used in the pre-test-post phase of this research. Cycle I includes planning and implementation (acting), observation (observing), and evaluating (evaluating) learning activities as well as reflection (reflecting).